Pengaruh Kompensasi terhadap Kinerja Karyawan di PT Bukit Raya Sekawan - Pratama, Yudhistira Anugerah; Yuliaty, Farida; Kosasih, Kosasih (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2025)
This study analyzes the effect of compensation on employee performance at Bukit Raya Sekawan Mining Company using an associative quantitative approach. The study population consists of all employees of the company, totaling 45 individuals. Data were collected through observations, interviews, literature studies, documentation, observation guidelines, and questionnaires. The results indicate that compensation has a positive influence on employee performance. Therefore, the company needs to monitor and evaluate both compensation and employee performance to optimize the achievement of corporate goals and employee welfare. Additionally, the company should provide clear information about the compensation system, particularly regarding health benefits. Thus, it is expected that the company and employees can jointly fulfill their objectives, rights, and obligations as a unified entity in the future